2020
DOI: 10.2478/fhort-2020-0015
|View full text |Cite
|
Sign up to set email alerts
|

Functional traits of okra cultivars (Chinese green and Chinese red) under salt stress

Abstract: Two okra cultivars (Chinese green and Chinese red) were subjected to salt stress for 12 weeks. Salt stress treatments T1 (20.8 mM), T2 (103.3 mM), T3 (180.0 mM) and T4 (257.0 mM) were applied with equal proportions of NaCl and CaCl2 in Hoagland nutrient solution. Salt stress significantly affects photosynthesis, transpiration, stomatal conductance, water use efficiency, water potential, plant height, root length, fresh weight and dry weight of both okra cultivars in every salt stress treatment. At T2, T3 and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
(40 reference statements)
0
9
1
Order By: Relevance
“…This is in tandem with studies by Temam et al [35] who reported differences in stem girths of various okra cultivars ranging from 14.5-30.5 cm in Ethiopia. These results contradict the findings of Azeem et al, [36] who reported an insignificant difference in stem girth among the various okra cultivars under his study.…”
Section: Evaluation Of the Adaptability Of Okra Cultivarscontrasting
confidence: 99%
“…This is in tandem with studies by Temam et al [35] who reported differences in stem girths of various okra cultivars ranging from 14.5-30.5 cm in Ethiopia. These results contradict the findings of Azeem et al, [36] who reported an insignificant difference in stem girth among the various okra cultivars under his study.…”
Section: Evaluation Of the Adaptability Of Okra Cultivarscontrasting
confidence: 99%
“…The use of saline water for irrigation on various crops, such as quinoa, okra, rice etc., has already been implemented (Azeem et al, 2020;Ibadzade et al, 2020;del Carmen Rodríguez-Hernández et al, 2021), but significantly less research has been done on the irrigation of medical herbs. Aktsoglou et al (2021) assessed the effect of mild salinity stress during the soilless cultivation of fresh peppermint and spearmint in a floating system on biomass yield, product quality and plant secondary metabolite content.…”
Section: Introductionmentioning
confidence: 99%
“…In squash, salinity is a factor that severely limits crop growth and productivity while at the same time deteriorating fruit quality. Despite the acquired knowledge in relation to the salt stress response in a plethora of plant species [ 33 , 38 , 39 ], there is a gap in relevant research fields for squash. Considering that the development of salt-tolerant germplasm is one of the most effective means for enhancing squash production in saline soils, this study aimed at investigating the response of squash germplasm to salt stress at the germination stage and examining the potential of selecting salt-tolerant genotypes at the laboratory level early.…”
Section: Introductionmentioning
confidence: 99%